Interpersonal interaction in infancy - Čepėnaitė-Užgirienė, I. (Psichologija, 1990)
Although parent-child interaction has been studied for a long time, it has not been viewed from an interpersonal perspective until recently. An interpersonal perspective reveals the communicative aspect of interpersonal interaction. The present paper considers the role of imitation during parent-child interaction in infancy and presents data on imitative sequences in mother- child communication. It is argued that imitation not only serves a communicative fun action, but also facilitates the construction of more complex interpersonal exchanges. Participation in these exchanges, in turn, enables the child to build schemata for more complex interaction patterns.
Keywords: interpersonal interaction; infancy; imitation